Micropropagação de Amburana cearensis (Allemão) A. C. Smith - Campos, Vania Celene Alecrim (2009)
Amburana cearensis (imburana-de-cheiro, camuru), belonging to the family Fabaceae-Papiolionoideae is a naturally occurring tree species in Caatinga. It is under threat due to over exploitation of its valuable timber and the medicinal use of its stem and seeds. The exploitation of extractive A. cearensis led this species to the list of endangered plants. In this context, the plant tissue culture is an important tool for conservation and propagation of native species, it enables the production of a large number of plants from a single individual. The objective the present work was to establish for in vitro protocol to multiplication of A. cearensis. It were evaluated the influence of different plant growth regulators (NAA, BAP and TDZ) on in vitro morphogenesis and different types of explants (leaflet, nodal segment, internodal segment, apical bud and cotyledonary segment). In the rooting stage were tested different concentrations of growth regulator IBA in the presence and absence of 1 g / L activated charcoal. The culture medium used in all experiments was the WPM supplied with 30g / L sucrose and 7g / L agar and pH adjusted to 5.7 ± 0.1 before autoclaving. The segment cotyledonary explant was considered the best for the stage of multiplication. Of the growth regulators tested, in the BAP concentration was 4.44 μM which gave the highest number of shoots (2.36). The explants leaflet and internodal segment showed no organogenic capacity. The rooted shoots better in the absence of activated charcoal. The highest number of roots was observed in medium supplemented with 10 μM of IBA. The survival rate of seedlings in acclimatization was 40%.